Modern approaches of EU countries to the circular economy - Kuzminska, Anastasiia; Korniienko, Iryna; Yastremska, Larysa; Kuznietsova, Olena; Baranovskyy, Mikhaylo (Problems of Environmental Biotechnology, 2024)
The modern approaches of the EU countries to the circular economy are considered